Caffeine increases muscle performance during a bench press training session - Giráldez-Costas, V.; González-García, J.; Lara, B.; Del Coso, J.; Wilk, M.; Salinero, J. J. (Journal of Human Kinetics, 2020)
Previous investigations have established the ergogenic effect of caffeine on maximal muscle strength, power output and strength-endurance. However, these investigations used testing protocols that do not replicate the structure of a regular strength training session. Thus, the aim of this study was to investigate the effect of acute caffeine ingestion on muscle performance during a simulated velocity-based training workout. In a double-blind, randomized and counterbalanced experiment, 12 participants performed two experimental trials after ingesting 3 mg/kg/b.m. of caffeine or a placebo. The trials consisted of 4 sets of 8 repetitions of the bench press exercise at 70% of their one-repetition maximum performed at maximal velocity. Bar velocity was recorded with a rotatory encoder and force, power output and work were calculated. Regarding the whole workout, caffeine increased mean bar velocity (+7.8%; p=0.002), peak bar velocity (+8.7%; p=0.006), mean force (+1.5%; p=0.002), mean power output (+10.1%; p=0.003) and peak power output (+8.2%; p=0.004) when compared to the placebo. The total work performed in the caffeine trial was superior to the placebo trial (7.01±2.36 vs 6.55±2.20 kJ, p=0.001). These results suggest that the acute intake of 3 mg/kg/b.m. of caffeine before a velocity-based strength workout increased muscle performance and the total work performed across the whole training session. Thus, caffeine can be considered as an effective strategy to enhance muscle performance during the bench press training sessions.